Психолого-педагогічні засади розвитку лідерських якостей учителів в освітньому середовищі початкової школи - Коломієць, Алла; Коломієць, Леся (Національний технічний університет "Харківський політехнічний інститут", 2019)
У статі схарактеризовано погляд на проблему розвитку лідерських якостей вчителів початкової школи крізь призму сучасних реформаційних процесів у галузі освіти. Розкрито ключові складові розуміння лідерства, його зміст і структуру, погляди вітчизняних і зарубіжних учених на класифікацію якостей ефективного вчителя-лідера, вивчено погляди сучасних педагогів, окремі складові їхнього лідерського потенціалу. Виявлено наявність розбіжностей між суб'єктивними уявленнями про лідерські якості й об'єктивним станом їх сформованості у вчителів. Визначено психолого-педагогічні засади розвитку лідерських якостей вчителів початкової школи. Зроблено висновок про необхідність прогнозування, проектування, моделювання супроводу розвитку лідерських якостей вчителів в освітньому середовищі початкової школи. Наголошено на доцільності використання з цією метою прогресивних педагогічних і сучасних інформаційно-комунікаційних технологій, потенціалу неформальної та інформальної освіти.

The article dealt the problem of development the leadership qualities of elementary school teachers through the prism of modern reform processes in the field of education. The key components of understanding of leadership, its contents and structure, modern views of domestic and foreign scientists on classification of teachers’ leadership qualities were revealed. The generalized ideas of elementary school teachers about the image of an effective teacher-leader and inherent leadership skills were analyzed and the individual components the teacher-leader’s leadership potential were examined. The discrepancies between subjective perceptions of leadership qualities and the objective state of their formation in teachers were revealed. The psychological and pedagogical principles of the development of elementary school teachers’ leadership qualities were defined. The need for forecasting, designing, simulation of modern leadership activity of elementary school teachers were emphasized. The authors summarized that forecasting, designing, modelling were necessary in accompanying the development of the leadership qualities of elementary school teachers. To realize this purpose the authors emphasized on expediency of using progressive pedagogical and modern information and communication technologies, the potential of informal education and self-education.
Psychological and pedagogical principles of the development of leadership qualities of teachers in the educational environment of elementary school
Keywords: супровід розвитку лідерських якостей; модернізація системи освіти; accompanying the development of the leadership qualities; modernization of the education system